COMPARISON OF (SVC/TCSC) - (STATCOM/SSSC) COMPENSATORS AND UPFC CONTROLLER IN NETWORK COUPLED TO WIND FARM USING JACOBIAN MATRIX IN NEWTON-RAPHSON ALGORITHM - Belatel, Mimi (Institute of Advanced Engineering and Science, 2020)
In recent years, the fast progress in the field and the application of the electronic system transmission plays an important role to make the system more reliable, controllable and efficient. It opened new opportunities for the application of the FACTS devices. The Flexible Alternating Current Transmissions System technology (FACTS) is used to have an optimal continuous power flow and open up new opportunities for controlling the electric system network. The UPFC (Unified Power Flow Controller) is one of the most versatile and complex power electric devices in the FACTS family. UPFC can control the active and the reactive power flow, a local bus voltage, it can also result a problem due to harmonics. In that regard, this paper presents a case study in which the PSAT software was implemented to comparing and analyzing the performance of the hybrid compensators namely (SVC/TCSC), (STATCOM/SSSC) and the UPFC in network coupled to wind farm. The Static Var Compensator (SVC) is a first shunt generation FACTS controller. TCSC (thyristor Controlled Series Capacitor) is consisted as a series compensating capacitor shunted by a thyristor controlled reactor. We can see that the UPFC controller has an effective power flow control, less setting time and less overshoot. The UPFC obtained a well known reputation for high controllability in power systems. The multilevel UPFC can be operated in STATCOM (Static Synchronous Compensator), in SSSC (Static Synchronous Series Compensator) and exactly in the UPFC mode. The results using Jacobian matrix in Newton-Raphson algorithm of UPFC are more significant compared to the hybrid (SVC/TCSC) and the (STATCOM/SSSC) controllers.